A study on the existence and uniqueness of a class of nonlinear fractional differential equations - Mohammed, Jasim Mohammed (Institute of Engineering Mathematics, 2018)
The aim of this study is to establish the existence and uniqueness of a class of fractional differential equations by achieving the following objectives; to obtain new results on the existence and uniqueness of fractional neutral differential equations; to obtain new results on the existence and uniqueness of fractional Rayleigh differential equations; to obtain new results on the existence and uniqueness of fractional neutral Rayleigh differential equations; to obtain new mathematical models in Biology and Psychotherapy problems.